The public health playbook: ideas for challenging the corporate playbook. Issue 7 (July 2022) - Lacy-Nichols, Jennifer; Marten, Robert; Crosbie, Eric; Moodie, Rob
Summary: Many commercial actors use a range of coordinated and sophisticated strategies to protect business interests—their corporate playbook—but many of these strategies come at the expense of public health. To counter this corporate playbook and advance health and wellbeing, public health actors need to develop, refine, and modernise their own set of strategies, to create a public health playbook. In this Viewpoint, we seek to consolidate thinking around how public health can counter and proactively minimise powerful commercial influences. We propose an initial eight strategies for this public health playbook: expand public health training and coalitions, increase public sector resources, link with and learn from social movements to foster collective solidarity, protect public health advocates from industry threats, develop and implement rigorous conflict of interest safeguards, monitor and expose corporate activities, debunk corporate arguments, and leverage diverse commercial interests. This set of strategies seeks to amplify inherent assets of the public health community and create opportunities to explicitly counter the corporate playbook. These strategies are not exhaustive, and our aim is to provoke further discussion on and exploration of this topic. Translation: For the Spanish translation of this paper see Supplementary Materials section.